Clinicopathological and molecular differences in colorectal cancer according to location. Issue 1 (March 2019) - Hsu, Yu-Lun; Lin, Chun-Chi; Jiang, Jeng-Kai; Lin, Hung-Hsin; Lan, Yuan-Tzu; Wang, Huann-Sheng; Yang, Shung-Haur; Chen, Wei-Shone; Lin, Tzu-Chen; Lin, Jen-Kou; Lin, Pei-Ching; Chang, Shih-Ching
Purpose: The incidence, pathogenesis, molecular pathways, and outcomes of colorectal cancer vary depending on the location of the tumor. This study aimed to compare the difference in tumor characteristics and the outcome between right-sided colon cancer and left-sided colorectal cancer (LCRC). Materials and methods: A total of 1503 patients with colorectal cancer who underwent surgery at the Taipei Veterans General Hospital between 2000 and 2010 were enrolled in this study. Right-sided colon cancer was defined as cancers in the cecum, ascending colon, and transverse colon, while LCRC was defined as cancers in the splenic flexure colon, descending colon, sigmoid colon, and rectum. The endpoint was overall survival. The mutations were detected via polymerase chain reaction and MASS array. The prognostic value was determined using the log-rank test and the Cox regression analysis. Results: A total of 407 and 1096 cases were classified as right-sided colon cancer and LCRC, respectively. Compared to patients with LCRC, those with right-sided colon cancer had more mucinous type cancer (7.4% vs. 3.5%), poorly differentiated tumor (11.5% vs. 3.6%), and advanced tumor-node-metastasis stage. The risk for peritoneal tumor seeding was higher in the right-sided colon cancer group (12.8% vs. 5.7%). Overall survival was better in LCRC than in right-sided colon cancer ( P =0.036). Conclusions: In our study, right-sided colon cancer had a more advanced tumor stage, a higher risk of peritoneal metastasis, and a poorer outcome than LCRC. Moreover, right-sided colon cancer had more gene mutations in BRAF, KRAS, SMAD4, TGF-β, PIK3CA, PTEN, AKT1, and high microsatellite instability.